2010
DOI: 10.1111/j.1440-1843.2010.01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Impulse oscillometry in preschool children and association with body mass index

Abstract: IOS is ideally suited to obtain measurements of respiratory function in preschool children. At the age of 6 years, standard oscillometric values do not indicate impaired respiratory function associated with increased BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
(41 reference statements)
1
23
0
2
Order By: Relevance
“…To date, there are few publications on the subject in different countries. More recent work identified by a review by Assumpção et al 31 include the studies by Park et al, 4 Dencker et al, 20 Amra et al, 22 Frei et al, 24 Kalhoff et al, 32 and Wee et al 33 . In 2015, most importantly, the study by GochicoaRangel et al 14 was carried out for the Latin American population.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are few publications on the subject in different countries. More recent work identified by a review by Assumpção et al 31 include the studies by Park et al, 4 Dencker et al, 20 Amra et al, 22 Frei et al, 24 Kalhoff et al, 32 and Wee et al 33 . In 2015, most importantly, the study by GochicoaRangel et al 14 was carried out for the Latin American population.…”
Section: Discussionmentioning
confidence: 99%
“…Nos estudos identificados na corrente revisão 5,34,35,43,58,60,61,62 , os valores de referência foram obtidos pela análise de regressão linear múltipla e transformações logarítmicas e identificam a estatura como o melhor fator preditivo para os parâmetros oscilométricos. 4 34 , analisou 222 crianças norte americanas, entre 3 e 10 anos.…”
Section: Valores De Referência Do Ios Para Faixa Etá-ria Pediátricaunclassified
“…39,12,14,38,41,62 Vem sendo constatada uma forte correlação entre algumas medidas do IOS e o VEF 1 , como nos estudos de Nowowiejska et al 38 e de Kalahoff et al 62 Vink et al 39 no qual, observaram que mudanças significativas na obstrução do fluxo aéreo foram identificadas por meio de correlações entre os valores de R e X com o VEF 1. Nos resultados obtidos por Song et al 41 as medidas de VEF 1 e PFE apresentaram correlação significativa com Z e R a 5, 10, 20 e 35 Hz, em asmáticos atópicos e em crianças saudáveis, sendo que as medidas de CVF também mostraram correlação com Z e com R em 10 Hz. A medida de FEF 25%-75% também teve correlação com parâmetro oscilométrico de X 18 , parecendo complementar informações fornecidas pelo VEF 1 .…”
Section: Relação Entre Ios E Outros Métodos De Avaliação Do Sistema Runclassified
“…In other words, clinical or epidemiological studies have probably involved heterogeneous groups of asthmatic phenotypes, which have different degrees of susceptibility to being overweight or for being overweight [43]. In preschool children, Kalhoff et al reported that no significant changes in R5 and X5 occurred with increases in BMI [44]. Shi et al also showed that R5-R20 or ALX had no correlation with BMI in school children [37].…”
Section: Discussionmentioning
confidence: 96%